Day 1 Wed, August 24, 2016 2016
DOI: 10.2118/181786-ms
|View full text |Cite
|
Sign up to set email alerts
|

Development of Seawater-Based Fracturing Fluid for High-Temperature Wells

Abstract: The development of a high-temperature seawater-based fracturing fluid has received much attention because it offers a solution to fresh water shortages; however, the rheological properties suffer significantly as a result of interactions between dissolved ions with fluid components. Various strategies have been investigated to address this challenge, including seawater treatments that ultimately remove the highly soluble and insoluble ionic moieties to yield a fracturing fluid with reliable rheological charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…In order to reduce the scaling propensity during fracturing treatments utilizing seawater-based fluid when combining with high TDS formation water, the nanofiltration (NF) of seawater was introduced. , It was discovered that the scaling issues during fracturing with seawater-based fluid may be effectively minimized by combining nanofiltration with the use of scale inhibitors, and it was determined that this combination is suitable for field applications. Nanofiltered seawater has been found to work well with scale inhibitors and is able maintain its rheological qualities for extended periods of time at temperatures as high as 350 °F. , In one study, it was found that no scale inhibitor was needed to produce negligible precipitation in mixtures of NF seawater and formation water. The reduced sulfate concentration of the NF seawater predicted a decrease in precipitates.…”
Section: Seawater-based Fracturing Fluid Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…In order to reduce the scaling propensity during fracturing treatments utilizing seawater-based fluid when combining with high TDS formation water, the nanofiltration (NF) of seawater was introduced. , It was discovered that the scaling issues during fracturing with seawater-based fluid may be effectively minimized by combining nanofiltration with the use of scale inhibitors, and it was determined that this combination is suitable for field applications. Nanofiltered seawater has been found to work well with scale inhibitors and is able maintain its rheological qualities for extended periods of time at temperatures as high as 350 °F. , In one study, it was found that no scale inhibitor was needed to produce negligible precipitation in mixtures of NF seawater and formation water. The reduced sulfate concentration of the NF seawater predicted a decrease in precipitates.…”
Section: Seawater-based Fracturing Fluid Developmentmentioning
confidence: 99%
“…Obtaining fresh water has become difficult in some fields due to the high water transportation costs from the source to the wellsite, as well as rising limits on freshwater supply . Conventional wells use 200 000 gallons of water for hydraulic fracturing, while unconventional wells can use up to 16 million gallons. For example, fracturing shale and tight sandstone formations often require more than 1 million gallons (3700 m 3 ) of water per well . This method uses a lot of water, damages the formation, and restricts future savings.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations